The measurement of a single-mode thermal field with a microwave cavity parametric amplifier - C Braggio; G Carugno; F Della Valle; G Galeazzi; A Lombardi; G Ruoso; D Zanello (New Journal of Physics, 2013)
In this paper, we present the experimental study of a single-mode thermal field carried out using a microwave parametric amplifier tuned at 1.5 GHz and working at room temperature. The parametric amplifier is based on a variable capacitance diode placed inside a microwave resonant cavity. The measured distribution of the thermal photons inside the resonator follows the expected Bose–Einstein distribution probability.